PROFIL KOMUNIKASI MATEMATIS SISWA SMP NEGERI 3 PALU DALAM MENYELESAIKAN SOAL CERITA LINGKARAN DITINJAU DARI GAYA BELAJAR - Nurafni, Nurafni; Hasbi, Muh.; Alfisyahra, Alfisyahra; Murdiana, I Nyoman (Universitas Tadulako, 2025)
This research aims to obtain a description of the mathematical communication of class VIII B students at SMP Negeri 3 Palu in solving circle story problems. This type of research is descriptive qualitative. The subjects of this research were students in class VIII B of SMP Negeri 3 Palu who had visual, auditory and kinesthetic learning styles. Data was collected through written assignments and interviews. The results of this research show that (1) The mathematical communication profile of visual subjects in solving circle story problems in indicator I; The subject writes down and is able to explain the information that is known and asked completely, using known mathematical symbols. In indicator II; The subject describes an illustration along with information on the illustration, and is able to explain how to draw an illustration of the question being asked. In indicator III; The subject is able to write down the formula he uses, write the formula that suits the question, namely the circle formula. Then, in the completion steps, the subject understands the multiplication of powers so that the answer obtained by the subject is correct. In indicator IV; The subject concludes the answer obtained at the end of the solution. On the V indicator; the subject concludes the results obtained correctly. In indicator VI; The subject gives a correct opinion regarding the results of solving the questions that have been worked on. (2) Mathematical communication profile of auditory subjects in solving circle story problems in indicator I; The subject writes down and is able to explain the information that is known and asked completely, using mathematical symbols to write down what is known. In indicator II; The subject describes an illustration along with information on the illustration, and is able to explain how to draw an illustration from the problem of the illustration being depicted. In indicator III; The subject is able to write and explain the formula, the formula written by the subject is the circle formula, then complete the steps in the problem being asked. In indicator IV; the subject is mistaken in adding up the final multiplication results of the question being asked, and does not conclude the answer obtained at the end of the solution. On the V indicator; the subject concludes the results obtained correctly. In indicator VI; The subject gives a correct opinion regarding the results of solving the questions that have been worked on. (3) Mathematical communication profile of kinesthetic subjects in solving circle story problems in indicator I; The subject writes and is able to explain the information that is known and asked about completely, even though he does not use mathematical symbols to write down what is known. In indicator II; The subject describes an illustration along with information on the illustration, and is able to explain how to draw an illustration of the question being asked. In indicator III; The subject can write and explain the formula he uses in solving the problem. Write down the appropriate formula to solve the problem. Write down the complete steps in solving the problem. But in indicator IV; The subject is mistaken in adding up the final product of the question being asked. And do not conclude the answers obtained at the end of the solution. On the V indicator; The subject concluded that he could not solve the problem correctly and the final results obtained were not accurate. In indicator VI; The subject gives a wrong opinion regarding the results of solving the questions that have been worked on.